Does the desaturase-2 locus in Drosophila melanogaster cause adaptation and sexual isolation? - Coyne, J.A.; Elwyn, S. (Evolution, 2006)
The desaturase-2 (desat2) locus of Drosophila melanogaster has two alleles whose frequencies vary geographically: one (the "Z" allele) is found primarily in east Africa and the Caribbean, and the other (the "M" allele) occurs in other parts of the world. It has been suggested that these alleles not only cause sexual isolation between races, but that their distribution reflects differential adaptation to climate: Z alleles are supposedly adapted to tropical conditions and M alleles to temperate ones. This has thus been viewed as a case of reproductive isolation evolving as a pleiotropic byproduct of adaptation. Here we reinvestigate this presumed climatic adaptation, using transgenic lines differing in the nature of their desat2 alleles. We were unable to replicate earlier results showing that carriers of M alleles are uniformly more cold resistant and less starvation resistant than carriers of Z alleles. It is thus doubtful whether the distribution of these alleles reflects natural selection involving climate. Mating studies of transgenic lines show some evidence for sexual isolation due to desat2. However, work on other, wild-type lines, as well as observations on the nature of sexual isolation, suggest that this conclusion--and thus the relationship between this locus and mating discrimination between races of D. melanogaster--may also be doubtful.